CT-MRI Dual Information Registration For The Diagnosis Of Liver Cancer: A Pilot Study Using Point-based Registration. - Aisyah Rahimi; Azira Khalil; Amir Faisal; Khin Wee Lai (Bentham Science Publisher, 2024)
Indexed by WOS/ Scopus